TEXTUAL ANALYSIS OF BUSTAN AS-SALIKIN - Iin Iin Maya Mairisa; Hermansyah (Indonesian Journal of Islamic History and Culture, 2021)
There are 2 manuscripts with the title Bustān As-Sālikīn at the Aceh State Museum, each with an inventory number of Manuscript Inv. 07.0065 (A) and the manuscript of Inv. 07.0807 (B). The purpose of this research is to produce text editing so that the text of the manuscript is read correctly and reveals its contents which are still very relevant to present and future life. The recent condition of manuscripts and the lack of research on the manuscripts are feared that the contents of the manuscripts will just be disappearing. The method used in this study is a combined method which includes an inventory of manuscripts, manuscript descriptions, text criticism, text editing, and a study of main ideas. The results of this study indicate that, firstly: from text editing, the text edition has been transliterated from Malay-Jawi Arabic letters to Latin script. Second: knowing clearly about the contents of the Bustān As-Sālikīn Manuscript which discusses the taṣawuf division which is divided into an opening, six chapters and a closing. Six chapters on purification of lust, educating children's behavior from an early age, elaboration and explanation of good behavior, people of the Tasawuf order, ways to fight lust, and finally the chapter on people who are deceived. The text also closes with a description of people who gain advantages by undergoing Taawuf tarekat by referring to the Tasawuf books.